Mechanical properties and microstructure of aramid/Al2O 3/epoxy resin laminated composites - Kumfu S. (2014)
Aramid/Al2O3/epoxy resin laminated composites were fabricated using ultrasonic mixing and casting technique. This novo material could be exhibited to the ideal mechanical properties such as high tensile strength, hardness, flexural strength and lightweight which may be used to replace metal parts in vehicles. Moreover, Al2O3 powder was mixed to epoxy resin to improve the scratch resistance. To improve the bending force and interaction between Al2O3 powder phase and epoxy resin phase, the ultrasonic mixing was used for fabricating these laminate composites. The physicals and mechanical properties such as density, hardness, impact test, wear resistance and tensile strength of the composites samples were investigated. It was found that the amounts of percent by volume of the Al2O3 have affected the properties of the laminated composites. Furthermore, microstructures of specimens were also investigated by scanning electron microscope (SEM). From the results, SEM images showed good distribution and adhesion between reinforced phase and epoxy resin matrix phase. © 2008 Trans Tech Publications, Switzerland.